The Enhancement of Uranium and Thorium in Bangka Tin Slag - S. Permana; J.W. Soedarsono; A. Rustandi; A. Maksum; K.S. Widana; K. Trinopiawan; M. Anggraini (Atom Indonesia, 2018)
Several researches have informed that air pollution, by-products, and residues in and waste products of natural resources exploitation and consumer goods contain uranium and thorium. In this research, the enhancement of these two metals resulted from the extraction process of Bangka tin slag. To deal with the enhancement of uranium and thorium, Bangka Tin Slag (BTS) was dissolved in Fluoric acid (HF), Chloric acid (HCl), and Sodium Hydroxide (NaOH). The result shows that Bangka tin slag has high contents of uranium, 3,404 ppm, and thorium, 25,850, which were achieved through the dissolution of BTS-roasting-quenching-sieving (BTS-RQS) residues in HF 8%, HCl 6M, and NaOH 10M.